Superficial angiomyxoma of the eyelid: a case report and review of the literature - Md Yusof, Nadzrin; Mohd Dusa, Noraini; Mohtarrudin, Norhafizah; Mohd Ali, Razana (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Superficial angiomyxoma (SA) is an angiomyxoid cutaneous tumour. It has predilection for the head and neck, torso, limbs and genital tract. Our case is a 27-year-old female, presented with painless right medial canthal mass for two years. It was associated with tearing when the lesion grew larger. We received a nodular brownish tissue measuring 25x20x15mm with homogenous brownish cut surface. Microscopically, the tumour was partially circumscribed, exhibiting bland stellate to spindle cells of moderate cellularity with pale eosinophilic cytoplasm, indistinct border, in a loose collagenous myxoid matrix with numerous blood vessels of different calibre. The lesional cells were present at the resected margin and were nonreactive towards CD34, SMA and S100. SA of the eyelid is sometimes mistaken clinically as dermoid cyst or lipoma. Reports have shown increased risks of local recurrence following incomplete excision. Close association with Carney’s complex is an important feature. Careful clinicopathologic correlation and proper investigations are needed for optimal patient care.